How Can Airport Service Quality Influence the Corporate Image: The Mediating Role of Customer Trust - Muhammad Thoriq Rabbani Irawan; Muhammad Fadhiil Fauzi Jayadita; Sandriana Marina; Amrulloh Ibnu Kholdun (Jurnal Siber Multi Disiplin, 2026)
Soekarno-Hatta International Airport still dominates the aviation market in the ASEAN region and is one of the busiest airports in the world. Hence, it needs to be balanced with the quality of airport services. This study analyzes Airport service quality's effect on corporate image mediated by customer trust at Soekarno-Hatta Airport Domestic Terminal 3. This research uses quantitative survey methods to collect data and surveys 259 Terminal 3 domestic Soekarno Hatta Airport passengers. The sampling method used is accidental sampling. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3 software. The results showed that airport service quality positively influences corporate image directly and through customer trust as a mediating variable.